DESAIN DIDAKTIS PADA KONSEP LUAS DAERAH TRAPESIUM UNTUK KELAS V SEKOLAH DASAR - Annizar, Edya Kresna; Suryadi, Didi (EduHumaniora | Jurnal Pendidikan Dasar Kampus Cibiru, 2016)
Abstract: This research was conducted in grade V, Cijambe Elementary School, Cibeber District, Cianjur regency, by using a qualitative approach through the method of Didactical Design Research (DDR). From the results of the initial study, the obstacles found to indicate the presence of ontological obstacles, didactical obstacles, and epistemological obstacles in learning trapezoid. The focus of the analysis is based on the theory of didactic situations, and the results of this analysis are used for the development of a didactic design hypothetic. Hypothetical didactic design is implemented to see how the didactic situations that developed during the learning followed by an analysis of the video transcript of learning outcomes of the implementation. The implementation results are analyzed again to obtain empirical didactic design, called retrosfektif analysis. Empirical didactic design composed of three lesson design. The first lesson design, consisting of three situations in which an action situation and formulations. Lesson second design, consisting of two situations in which an action situation, formulation and validation. Lesson third design, consisting of four situations are situations of action, the situation formulation, validation situation, and the situation institutionalization.Keywords: Didactical Design Research, Learning Obstacle, Didactical Design, Trapezoid.Â Abstrak: Penelitian ini dilaksanakan di Kelas V Sekolah Dasar Negeri Cijambe Kecamatan Cibeber Kabupaten Cianjur dengan menggunakan pendekatan kualitatif melalui metode DDR (Didactical Design Research). Dari hasil studi awal, hambatan yang ditemukan menunjukkan adanya ontogenical obstacles, didactical obstacles, dan epistemological obstacles pada pembelajaran trapesium. Fokus analisis berdasarkan teori situasi didaktis, dan hasil analisis ini digunakan untuk pengembangan desain didaktis hipotetik. Desain didaktis hipotetik diimplementasikan untuk melihat bagaimana situasi-situasi didaktis yang berkembang selama pembelajaran dilanjutkan dengan analisis terhadap transkrip video pembelajaran hasil implementasi. Hasil implementasi dianalisis lagi untuk mendapatkan desain didaktis empirik, yang disebut analisis retrosfektif. Desain didaktis empirik yang tersusun terdiri dari tiga pertemuan (lesson design). Lesson design pertama, terdiri dari tiga situasi yang merupakan situasi aksi dan formulasi. Lesson design kedua, terdiri dari dua situasi yang merupakan situasi aksi, formulasi, dan validasi. Lesson design ketiga, terdiri dari empat situasi yang merupakan situasi aksi, situasi formulasi, situasi validasi, dan situasi institusionalisasi.Kata kunci: Didactical Design Research, Learning Obstacle, Desain Didaktis, Trapesium